A Robust and Rapid Candidate Gene Mapping Pipeline Based on M2 Populations - Zhou, Huangkai; Tang, Kuanqiang; Li, Guang; Liu, Wenqiang; Yu, Hui; Yuan, Xiaohui; Yang, Suxin; Bhattacharyya, Madan K.; Feng, Xianzhong (Frontiers in Plant Science, 2021)
The whole-genome sequencing-based bulked segregant analysis (WGS-BSA) has facilitated the mapping candidate causal variations for cloning target plant genes. Here, we report an improved WGS-BSA method termed as M2-seq to expedite the mapping candidate mutant loci by studying just M2 generation. It is an efficient mutant gene mapping tool, rapid, and comparable to the previously reported approaches, such as Mutmap and Mutmap+ that require studying M3 or advanced selfed generations. In M2-seq, background variations among the M2 populations can be removed efficiently without knowledge of the variations of the wild-type progenitor plant. Furthermore, the use of absolute delta single-nucleotide polymorphism (SNP) index values can effectively remove the background variation caused by repulsion phase linkages of adjacent mutant alleles; and thereby facilitating the identification of the causal mutation in target genes. Here, we demonstrated the application of M2-seq in successfully mapping the genomic regions harboring causal mutations for mutant phenotypes among 10 independent M2 populations of soybean. The mapping candidate mutant genes just in M2 generation with the aid of the M2-seq method should be particularly useful in expediting gene cloning especially among the plant species with long generation time.